IMPLEMENTING VALUES OF LOCAL WISDOM IN MANAGING THE BUDGETS OF RURAL FINANCING AT PORINGAN VILLAGE IN WEST SULI DISTRICT OF LUWU REGENCY - Kamal, Helmi; Jerianto, Jerianto (Islamic Economics and Business Faculty of UIN Antasari, 2018)
The focus of this article is to explore the practical concepts of local wisdom values in managing the budgets of Rural financing at Poringan Village in West Suli District of Luwu Regency. This study also highlights the inhibiting factors for the implementation of local wisdom values in managing the budget of rural financing. For such purposes, this research applies qualitative research that enables the analysis of field evidence-based data without the involvement of statistical and numeric analysis. This study found that there were three fundamental values of local wisdom practiced in the management of budgets of rural financing. The values were concepts related to adele (just), lempu (honest) and getting (persistent).